CAFFEINE AND PERFORMANCE IN ENDURANCE SPORTS: A SYSTEMATIC REVIEW OF THE LITERATURE - Maia Neto, José Dalvo; Ferreira, Heraldo Simões; Assunção Neto, Marcos Vinícius (Seven Editora, 2026)
Introduction: Caffeine is one of the most studied and widely used ergogenic substances by endurance athletes, with consistent evidence of improved physical performance. Objective: To conduct a systematic review of the literature on the effects of caffeine supplementation on the performance of athletes in endurance sports, analyzing dosages, timing of administration, mechanisms of action, and possible adverse effects.Methods: A systematic search was performed in PubMed, Scopus, Web of Science, and SPORTDiscus databases, using the descriptors 'caffeine', 'endurance', 'performance', 'supplementation', and 'athletes'. Randomized clinical trials published between 2010 and 2024 involving endurance athletes were included.Results: 47 studies met the inclusion criteria. Caffeine supplementation (3-6 mg/kg) significantly improved performance in endurance events (p